Perbandingan Perkembangan Pendirian Perseroan Terbatas Di Indonesia Dan Belanda - Laksana, Khrisna Adjie; Sendrawan, Tjhong (Universitas Semarang, 2023)
The aim of this research is to compare the development of the establishment of Limited Liability Companies in Indonesia and the Netherlands along with the development of society. Regulations regarding Limited Liability Companies in Indonesia have undergone several changes, which are currently regulated in Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 11 of 2020 concerning Job Creation which introduces a new form of Company, namely Individual Companies, changes to the law -The law intends to be more in line with current legal developments so that it can accommodate the needs of the community. This writing has an urgency, namely that along with developments over time, of course regulations will also change along with the needs of society. This research compares the consistency of the development and application of regulations in Indonesia and the Netherlands with the aim of learning and developing in the legal field. This research method uses normative juridical research methods. This research has a novelty, namely a discussion related to the comparison regarding the establishment of limited liability companies in Indonesia and in the Netherlands and comparing the consistency regarding changes that are still in accordance with legal principles. The results of this research are that in the Netherlands there are differences with Indonesia, namely related to the status of individual companies, in which case Indonesia has the status of a legal entity, whereas in the Netherlands individual companies are not legal entities. Another difference between the Netherlands and Indonesia that can be seen is the same regarding approval from the government to establish a company, in the Netherlands starting in 2011, the provisions for government approval have been removed and replaced with a system of strict supervision by the ministry. Tujuan dari penelitian ini adalah membandingkan mengenai perkembangan pendirian perseroan terbatas di Indonesia dengan Belanda seiring perkembangan masyarakat. Pengaturan mengenai perseroan terbatas di Indonesia sudah mengalami beberapa kali perubahan yang mana saat ini diatur dalam Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas dan Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja yang mengenalkan suatu bentuk perseroan baru yakni perseroan perseorangan, perubahan undang-undang tersebut bermaksud agar lebih sesuai dengan perkembangan hukum saat ini sehingga dapat mengakomodir kebutuhan dari masyarakat. Penelitian ini memiliki urgensi yaitu seiring dengan perkembangan zaman, tentunya peraturan juga akan berubah seiring dengan kebutuhan masyarakat, penelitian ini membandingkan bagaimana konsistensi dari perkembangan dan penerapan peraturan di Indonesia dengan Belanda dengan tujuan sebagai pembelajaran dan pengembangan dalam bidang hukum. metode penelitian ini menggunakan metode penelitian doktrinal. Penelitian ini mempunyai kebaruan yaitu pembahasan terkait perbandingan mengenai pendirian perseroan terbatas di Indonesia dan Belanda dan membandingkan bagaimana konsistensi terkait perubahan yang masih sesuai dengan prinsip-prinsip hukum. Hasil dari penelitian ini yaitu di Belanda memiliki perbedaan dengan Indonesia, yaitu terkait dengan status perusahaan perseorangan yang mana dalam hal ini Indonesia memiliki status sebagai badan hukum, sementara di Belanda perusahaan perseorangan bukanlah badan hukum. Perbedaan lain antara Belanda dan Indonesia yang dapat dilihat dalam halnya terkait persetujuan dari pemerintah untuk mendirikan perseroan, di Belanda mulai pada tahun 2011 telah menghapus ketentuan persetujuan pemerintah dan menggantikannya dengan sistem pengawasan yang ketat oleh kementerian.